The Influence of Service Quality, InformationQuality, and System Quality on Perceived Value on Customer Satisfaction - Pitaloka, Olivia Inger; Indradewa, Rhian (Publikasi Indonesia, 2025)
This study aims to evaluate the influence of Service Quality, Information Quality, and System Quality on Customer Satisfaction mediated by Perceived Value in the context of e-learning usage among students in Java. The research background highlights the importance of enhancing student satisfaction with e-learning to support the effectiveness of online learning processes. This research employed a quantitative approach using Structural Equation Modeling –Partial Least Squares (SEM-PLS). The research sample comprised 137 active students utilizing e-learning platforms from universities in Java. The results indicated that Service Quality, Information Quality, and System Quality significantly influenced Perceived Value. Service Quality and System Quality had a significant effect on Customer Satisfaction, whereas Information Quality did not directly impact Customer Satisfaction significantly. The study recommends that universities improve system and service quality and enhance information quality in e-learning platforms to increase Perceived Value and student satisfaction. This research contributes deeper insights for university management to effectively manage e-learning platforms and enhance student satisfaction